Protective role of BST2 polymorphisms in mother-to-child transmission of HIV-1 and adult AIDS progression - Kamada, Anselmo Jiro (J Acquir Immune Defic Syndr, 2016)
BST-2/Tetherin is a restriction factor that prevents Human immunodeficiency virus type 1 (HIV-1) release from infected cells and mediates pro-inflammatory cytokine production. This study investigated the risk conferred by single nucleotide polymorphisms (SNPs; rs919266, rs9192677 and rs9576) at BST-2 coding gene (BST2) in HIV-1 mother-to-child transmission and in disease progression. Initially, 101 HIV-1+ pregnant women and 331 neonates exposed to HIV-1 from Zambia were enrolled. Additional BST2 SNPs analyses were performed in two cohorts with acquired immunodeficiency syndrome (AIDS) progression: an adult Brazilian cohort (37 rapid, 30 chronic and 21 long-term non-progressors) and an Italian pediatric cohort (21 rapid and 67 slow progressors). The rs9576A allele was nominally associated with protection during breastfeeding (p=0.019), and individuals carrying rs919266GA showed slower progression to AIDS (p=0.033). Despite the influence of rs919266 and rs9576 in BST2 expression is still undetermined, a preventive role by BST2 polymorphisms was found during HIV-1 infection.